Analysis, Philosophy and the Challenge of Critical Theory: Michael Spitzer’s Music as Philosophy: Adorno and Beethoven’s Late Style - Horton, Julian (Journal of the Society for Musicology in Ireland, 2007)
Michael Spitzer’s Music as Philosophy: Adorno and Beethoven’s Late Style (Indiana University Press, 2006, ISBN 0-253-34724-6) pursues multiple lines of scholarly enquiry. As a musicological study, the book advances an historicist agenda, which grounds the understanding of Beethoven’s music in an extension of its contemporaneous philosophical context. As a music-analytical study, it proposes an approach based on fluid philosophical and style-historical categories, and so opposes the quasi-scientific, theory-heavy strategies that increasingly dominate transatlantic music analysis. As a template for current scholarly practice, Music as Philosophy fights a rearguard action against the postmodern opprobrium that Adorno and his descendents have recently endured. This review article evaluates Spitzer’s study against the background of recent critical engagements with Adorno’s legacy, especially that advanced by Richard Taruskin, estimating the analytical efficacy of Spitzer’s Adornian apparatus, and appraising the defence of critical theory it mounts, in view of the postmodern hostility such modes of thought have of late provoked.